Hitoribotchi no yell : best collection II - Anzenchitai; Polygram Records (Hong Kong : PolyGram Records, 1994)
Terdapat lima belas buah lagu berbahasa Jepun yang dimuatkan dalam album ini.
CD 1 : Moegiiro no Snap / (5:17) -- Mayonakasugi no Koi / (3:55) -- Anata ni / (3:51) -- Masquerade / (4:06) -- Kanashimi ni Sayonara / (4:32) -- Gin Iro no Pistol / (3:44) -- Juliet / (3:55) -- Tsuki ni Nureta Futari / (4:42) -- Too Late Too Late / (4:06) -- Ano Natsu wo Oikakete / (3:47) -- Jounetsu / (3:34) -- Itsumo Kimi no Sobani / (5:30) -- Asa no Hizashi ni Kimi ga ite / (4:22) -- Anokoroe / (4:57) -- Hitoribotchi no Yell / (6:42).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, Japanese; Popular music -- Japan